Quwatanabius Smetana—a new genus in the fauna of the Mainland China (Coleoptera, Staphylinidae), with description of two new species - Hu, Jiayao; Li, Lizhen; Zhao, Meijun (Zootaxa, 2012)
The genus Quwatanabius was established by Smetana (2002) to hold two species that were previously assigned to Quedius Stephens: the type species Quwatanabius flavicornis (Sharp, 1889) recorded from Japan and Taiwan, and Qu. chiaw (Smetana, 1995) from Taiwan. The genus may be distinguished from other genera of Quediina by the elongate apical segments of both maxillary and labial palpi that are as long as the two preceding segments combined. To date, no species of Quwatanabius has been recorded from the mainland China. During our recent collecting trips, two new species of the genus were found in Guangdong and Zhejiang Provinces. The purpose of this paper is to describe and illustrate these two new species, and to provide an identification key to all four currently known species of Quwatanabius.